2023
DOI: 10.1037/tep0000375
|View full text |Cite
|
Sign up to set email alerts
|

Survey of doctoral internships in psychology offering experience in forensics and corrections.

Abstract: Students with forensic/correctional interests seek out related doctoral internship sites, though often without clear, updated information on what these sites desire of applicants. To clarify student experiences and qualities most valued by these internships. We identified internship sites reporting "forensic/correctional experience" via a public internship directory (N = 164). We gathered site information from directory pages and sent an online survey to the sites' internship directors. Internship directors (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Magaletta et al (2013) surveyed 170 APA-accredited psychology doctoral programs and found that 111 (65%) offered experience in corrections, and a follow-up study showed that intervention comprised the majority of corrections practicum experience (Magaletta et al, 2017). The number of predoctoral psychology internships with correctional or forensic components have tripled over the last decade (Malesky & Croysdale, 2009; Potts et al, 2020). Forensic e-mental health provides a novel avenue for training and supervising students interested in this career trajectory.…”
Section: Policy Directionsmentioning
confidence: 99%
“…Magaletta et al (2013) surveyed 170 APA-accredited psychology doctoral programs and found that 111 (65%) offered experience in corrections, and a follow-up study showed that intervention comprised the majority of corrections practicum experience (Magaletta et al, 2017). The number of predoctoral psychology internships with correctional or forensic components have tripled over the last decade (Malesky & Croysdale, 2009; Potts et al, 2020). Forensic e-mental health provides a novel avenue for training and supervising students interested in this career trajectory.…”
Section: Policy Directionsmentioning
confidence: 99%